2021
DOI: 10.3390/jcm10235716
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Periprocedural Clinical Factors Related to the Course of STEMI in Men and Women Based on the National Registry of Invasive Cardiology Procedures (ORPKI) between 2014 and 2019

Abstract: Background: There are several sex-related differences in the course, management, and outcomes of ST-elevation myocardial infarction (STEMI). This study aimed to identify the risk factors that may affect the odds of procedure-related death in patients with STEMI. Methods: The observational cohort study group consisted of 118,601 participants recruited from the National Registry of Invasive Cardiology Procedures (ORPKI). Results: Procedure-related death occurred in 802 (1.0%) men and in 663 (1.7%) women. The odd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…The analysis of a large number of variables in scientific studies requires the creation of new statistical tools. Logistic regression seems to be a promising tool in this analysis and has been successfully used by authors [ 28 , 49 ]. An even more interesting statistical tool for the analysis of large amounts of data with the use of long-term databases is the creation of neural networks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of a large number of variables in scientific studies requires the creation of new statistical tools. Logistic regression seems to be a promising tool in this analysis and has been successfully used by authors [ 28 , 49 ]. An even more interesting statistical tool for the analysis of large amounts of data with the use of long-term databases is the creation of neural networks.…”
Section: Discussionmentioning
confidence: 99%
“…A study of patients with ACS and the impact of vaccination was presented by our research team in another paper [ 26 ]. Correlations between acute coronary syndromes and various clinical, peri-procedural, and environmental factors have been studied by our team for several years [ 15 , 27 , 28 ]. The current work presents for the first time the correlations between environmental factors (air pollution and COVID-19 infection).…”
Section: Methodsmentioning
confidence: 99%
“…Electronic data were collected from patients with acute coronary syndromes who underwent invasive cardiology procedures. This study included data from patients enrolled in the register between 2014 and 2021 [ 8 , 9 ]. We determined the number of patients undergoing PCI following admission with ACS (STEMI, NSTEMI, or UA) during the day of autumn and spring time change.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have consistently reported that female patients with acute myocardial infarction (AMI) have higher unadjusted mortality rates than men, especially for short-term follow-up [1,2]. Women present with AMI at a later age, with greater cardiovascular risk burdens, and with less opportunity to receive guideline-recommended therapies.…”
Section: Introductionmentioning
confidence: 99%